Live Longer, Work Longer: Making It Happen in the Labor Market - Vodopivec, Milan (2012)
An aging population and the corresponding shrinkage of the labor force will create a significant drag on economic growth and may jeopardize the economic well-being of some of the elderly. Thus working longer is an imperative--but extending working lives has proven difficult, both because workers do not want to work longer and because employers are lukewarm about employing older workers. As measures that can be taken to motivate workers to work longer, the paper proposes providing retirement incentives and attractive, flexible working arrangements. To induce employers to hire old workers, it suggests removing the obstacles imposed by restrictive labor market institutions, an increase in the human capital of workers via life-long learning, and addressing age-discrimination. Chances for extending working lives will also increase as the health of elderly workers is improved.